The effect of sintering temperature and copper substitution on the structural and magnetic properties of nickel-zinc ferrite - G. Ahmadpour (Journal of Advanced Materials in Engineering, 2013)
The particles of ferrite Ni0.6-xCuxZn0.4Fe2O4, (0-0.5 in step with 0.1) were prepared by the sol-gel method. Sintering process of powders was carried out at 600, 800 and 1000 oC. The effect of the sintering temperature and chemical composition on the structural and magnetic properties of the Cu substituted NiZn ferrite was investigated. EDS analysis and X-ray diffraction patterns confirmed a well defined of single crystal phase with spinel structure. The thermal behavior process and particle size of samples were investigated by thermal analysis TG, DTA techniques and scanning electron microscope, respectively. VSM curves reveal that the sintering temperature and copper content affect saturation magnetization. M ssbauer spectra displays that the copper cations occupy the octahedral sites. With increasing of copper cations, the iron cations immigrate to tetrahedral site, consequently the saturation magnetization decrease.